Evolution of Specialization of Cassida rubiginosa on Cirsium arvense (Compositae, Cardueae) - Cripps, Michael G.; Jackman, Sarah D.; Roquet, Cristina; van Koten, Chikako; Rostás, Michael; Bourdôt, Graeme W.; Susanna, Alfonso (Frontiers in Plant Science, 2016)
The majority of herbivorous insects are specialised feeders restricted to a plant family, genus, or species. The evolution of specialised insect-plant interactions is generally considered to be a result of trade-offs in fitness between possible hosts. Through the course of natural selection, host plants that maximise insect fitness should result in optimal, specialised, insect-plant associations. However, the extent to which insects are tracking plant phylogeny or key plant traits that act as herbivore resistance or acceptance characters is uncertain. Thus, with regard to the evolution of host plant specialisation, we tested if insect performance is explained by phylogenetic relatedness of potential host plants, or key plant traits that are not phylogenetically related. We tested the survival (naive 1st instar to adult) of the oligophagous leaf-feeding beetle, Cassida rubiginosa, on 16 selected representatives of the Cardueae tribe (thistles and knapweeds), including some of the worst weeds in temperate grasslands of the world in terms of the economic impacts caused by lost productivity. Leaf traits (specific leaf area, leaf pubescence, flavonoid concentration, carbon and nitrogen content) were measured as explanatory variables and tested in relation to survival of the beetle, and the phylogenetic signal of the traits were examined. The survival of C. rubiginosa decreased with increasing phylogenetic distance from the known primary host plant, C. arvense, suggesting that specialisation is a conserved character, and that insect host range, to a large degree is constrained by evolutionary history. The only trait measured that clearly offered some explanatory value for the survival of C. rubiginosa was specific leaf area. This trait was not phylogenetically dependant, and when combined with phylogenetic distance from C. arvense gave the best model explaining C. rubiginosa survival. We conclude that the specialisation of the beetle is explained by a combination of adaptation to an optimal host plant over evolutionary time, and key plant traits such as specific leaf area that can restrict or broaden host utilisation within the Cardueae lineage. The phylogenetic pattern of C. rubiginosa fitness will aid in predicting the ability of this biocontrol agent to control multiple Cardueae weeds.